An Assessment of Maximal Isometric Hand Grip Strength and Upper Body Explosive Strength and Endurance in Various Ball Sports - Md Hamidur Rahman; J. P. Sharma (OVS LLC, 2023)
Background. Playing with the ball and using hand-arm strength and power are very crucial for ball game players. It takes arm force and endurance, as well as isometric hand grip strength, to accomplish ball-game skills. Study purpose. The aim of the study was to evaluate maximal isometric hand grip strength, arm and shoulder explosive strength, and endurance in basketball, handball, and volleyball athletes. Materials and methods. The study randomly selected 135 male athletes, including 45 basketball, 45 handball, and 45 volleyball players, aged 17 to 24, all competing at the inter-university level. Hand grip strength (HGS) for both dominant (DHGS) and non-dominant (NDHGS) hands was measured using a JAMAR hydraulic hand grip dynamometer. An over-the-head seated medicine ball throw (SMBT) test assessed explosive arm strength, while a push-up (PU) test evaluated muscular strength and endurance. Results. The F-values (F) (2, 132) of DHGS, NDHGS, SMBT, and PU tests among basketball, handball, and volleyball players were .499 (p = .608); 1.166 (p = .315); 5.595 (p = .005); and 10.339 (p = .000), respectively. The results indicated that no notable distinctions were observed in DHGS and NDHGS among athletes in the three sports. However, considerable differences were found in the SMBT and PU tests. Conclusions. The study concluded that basketball, handball, and volleyball players' maximum isometric hand grip strength was nearly the same, but in both cases, the handball player's mean value was superior to others. Upper-body explosive power, muscular strength, and endurance showed distinct differences from one group to another.